Home » Blog » Verify some formulas for the function g(x) = (4-x^2)^(1/2)

Verify some formulas for the function g(x) = (4-x^2)^(1/2)

Let g(x) \sqrt{4-x^2} for |x| \leq 2.

  1. g(-x) = g(x).
  2. g(2y) = 2 \sqrt{1-y^2}.
  3. g(1/t) = \frac{\sqrt{4t^2-1}}{|t|}.
  4. g(a-2) = \sqrt{4a-a^2}.
  5. g(s/2) = \frac{1}{2} \sqrt{16-s^2}.
  6. \frac{1}{2+g(x)} = \frac{2-g(x)}{x^2}.

  1. Proof.
    g(-x) = \sqrt{4-(-x^2)} = \sqrt{4-x^2} = g(x). Valid for |x| \leq 2. \qquad \blacksquare
  2. Proof.
    g(2y) = \sqrt{4-(2y)^2} = \sqrt{4-4y^2} = 2 \sqrt{1-y^2}. Valid for |y| \leq 1. \qquad \blacksquare.
  3. Proof.
    \displaystyle{ g(1/t) = \sqrt{4 - \left( \frac{1}{t} \right)^2} = \sqrt{\frac{1}{t^2}(4t^2 - 1)} = \frac{\sqrt{4t^2-1}}{\sqrt{t^2}} = \frac{\sqrt{4t^2-1}}{|t|}}. Valid for |t| \geq \frac{1}{2}. \qquad \blacksquare
  4. Proof.
    g(a-2) = \sqrt{4-(a-2)^2} = \sqrt{4-a^2 + 4a - 4} = \sqrt{4a - a^2}. Valid for 0 \leq a \leq 4. \qquad \blacksquare
  5. Proof.
    \displaystyle{g \left( \frac{s}{2} \right) = \sqrt{4-\frac{s^2}{4}} = \frac{1}{2} \sqrt{16-s^2}}. Valid for |s| \leq 4. \qquad \blacksquare
  6. Proof.
    \displaystyle{\frac{1}{2+g(x)} = \frac{1}{2+\sqrt{4-x^2}} = \frac{2-\sqrt{4-x^2}}{4-4+x^2} = \frac{2-g(x)}{x^2}}. Valid for 0 < |x| \leq 2. \qquad \blacksquare

Point out an error, ask a question, offer an alternative solution (to use Latex type [latexpage] at the top of your comment):